Scottish outcomes for extra hepatic biliary atresia post-rationalisation of services. Issue 5 (21st February 2013) - Tayler, Rachel; Barclay, Andrew R; Rogers, Pam; Mcintyre, Karen; Russell, Richard K; Devadason, David; Bisset, W Mike; Ling, Simon C; McGrogan, Paraic
Abstract : Aims: To evaluate the outcome of Scottish children with extra hepatic biliary atresia (EHBA) since rationalisation of Kasai services to three English centres in 2002 (The 'Group A' centres). Methods: All Scottish children with EHBA diagnosed between 2002 and 2009 were identified via the Scottish Society of Paediatric Gastroenterology, Hepatology and Nutrition (SSPGHAN) clinicians. A case-note review was conducted with demographics, presentation and outcome data recorded. These data were compared with historical Scottish data and data published previously by the supraregional liver units. Results: 25 patients were identified, of whom 22 were referred for Kasai in the group A centres, and of whom 19 had a Kasai. 2 year transplant-free survival (TFS) was significantly lower in the SSPGHAN 2002–2009 group than the group A centres in (1) (6/18 (33%) vs 36/57 (63%), p=0.023). Conclusions: These postrationalisation data are disappointing. The emphasis for care will now focus on improved communication between, primary care, general paediatricians and surgical centres through regional and national managed clinical networks, aiming to improve future outcomes for Scottish children with BA.